Concurrent Babesia Bigemina and Anaplasma Marginale Infection in a Jersey Cow - Mohanapriya, T.; Pazhanivel, N.; Enbavelan , P.A.; Kumar , V. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Haemoprotozoan diseases cause devastating losses to the livestock industry and hence pose major constraints to the dairy industry. Bovine babesiosis and anaplamosis is a tick – borne, parasitic infection that causes significant morbidity and mortality. The present paper reports on the occurrence of concurrent Babesia bigemina and Anaplasma marginale infection in a Jersey cow in Tirunelveli city, Tamil Nadu.